The recent 2021 Yerevan earthquake (ml=4.9) in the seismotectonic context of the Yerevan fault - Sargsyan, L.; Sahakyan, E.; Levonyan, A.; Demirchyan, H.; Toghramadjian, N.; Gevorgyan, M.; Bayraktutan, M. S. (ՀՀ ԳԱԱ)
The earthquake of February 13, 2021 earthquake was the strongest earthquake ever reported in the vicinity of Armenia’s capital city of Yerevan in the modern instrumental time period. It was strongly felt throughout Yerevan and the surrounding areas. In this study, we analyze the source parameters and focal mechanism of this earthquake. Our calculated focal mechanism solution shows that this 2021 M4.9 earthquake is characterized by a thrust fault mechanism with a strike-slip component. We also discuss historical seismicity that has occurred over the course of a century in direct proximity to Yerevan, and demonstrate that the Yerevan Fault and Parakar sub-fault are seismically active systems. We also address the problem of possible NW and SE extensions of the Yerevan fault. Ժամանակակից գործիքային ժամանակաշրջանում՝ 2021թ փետր-վարի 13-ի երկրաշարժը, ըստ հաղորդագրությունների, ամենաուժեղն էր Հայաստանի մայրաքաղաք Երևանում երբևիցե տեղի ունեցածներից: Այն ուժեղ զգացվում էր ամբողջ Երևանում և նրա շրջակայքում: Վերածվել է երկրաշարժի օջախի պարամետրերը և ֆոկալ մեխանիզմը: Մեր կողմից հաշվարկված ֆոկալ մեխանիզմը ցույց է տալիս, որ 2021թ M4.9 մագնիտուդով այդ երկրաշարժը բնութագրվում է կողաշարժի բաղադրիչ ունեցող վրաշարժի խզվածքի մեխանիզմով: Այդ, քննարկվել է Երևանի անմիջական մոտակայքում մեկ դարի ընթացքում տեղի ունեցած պատմական սեյսմիկությունը և ցույց է տրվել, որ Երևանյան խզվածքը և Փարաքարի ենթախզվածքը սեյսմիկորեն ակտիվ համակարգեր են: Անդրադարձ է կատարվել Երևանյան խզվածքի հնարավոր Հս.-Արմ. և Հվ.-Արլ. շարունակության խնդրին: По сообщениям за современный инструментальный период времени землетрясение 13 евраля 2021 года было самым сильным событием в окрестности столицы Армении – Еревана. Оно сильно ощущалось по всему Еревану и на окружающих территориях. В данном исследовании мы анализируем параметры очага и окальный механизм этого землетрясения. аш расчет окального механизма показывает что это землетрясение 2021г. с магнитудой M4.9 характеризуется надвиговым механизмом с компонентой сдвига. Мы также обсуждаем историческую сейсмичность за столетие в непосредственной близости к Еревану и показываем что Ереванский разлом и Паракарский субразлом являются сейсмически активными системами. Мы также рассматриваем проблему продолжения Ереванского разлома на СЗ и на ЮВ.
Keywords: Geophysics